(untitled) (Research, Society and Development, 2021)
This study analyzes the influence of sustainable consumption habits and environmental awareness on the intention to purchase ecological products. This is a survey that was carried out with 299 teachers who work in the public education system in the cerrado of Piauí. Descriptive analysis, exploratory factor analysis, and multiple linear regression techniques were applied in the data analysis. The results indicate that sustainable consumption habits and environmental awareness influence the intention to purchase ecological products, specifically by the variables “healthy products” and “growth limit”. It indicates that the individuals who attach greater importance to the consumption of healthy products and are concerned with the limits of production, consumption, and growth tend to have a greater intention to purchase ecological products. Besides, it was found that the variables gender, age group, child(ren), and income affected the intention to purchase ecological products. The research contributes to the field of sustainable development as it fosters the discussion on sustainable attitudes and behaviors of teachers, who are key professionals in the process of developing environmental education practices in school spaces, contributing to the critical and social education of students, focusing on sustainability. Thus, this study helps to broaden the academic debate on the subject in question, motivating researchers to investigate other issues related to sustainability in the educational context.